2014
DOI: 10.1007/s11427-014-4681-7
|View full text |Cite
|
Sign up to set email alerts
|

Cascade effects of crop species richness on the diversity of pest insects and their natural enemies

Abstract: Understanding how plant species richness influences the diversity of herbivorous and predatory/parasitic arthropods is central to community ecology. We explore the effects of crop species richness on the diversity of pest insects and their natural enemies. Using data from a four-year experiment with five levels of crop species richness, we found that crop species richness significantly affected the pest species richness, but there were no significant effects on richness of the pests' natural enemies. In contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Reasonable mixtures of different crop cultivars can alleviate the limitations triggered by monoculture and low biodiversity (Van & Harfington, ) and enhance the natural enemy species richness (Shi et al ., ). It has been suggested that the increase in crop diversity in agricultural landscape configuration contributes to a general decrease in pest damage on crops (Chaplin‐Kramer et al ., ; Gagic et al ., ); the effect may range from localized reduction of pest abundance to a lower general equilibrium of pest populations at the landscape level (Jonsson et al ., ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Reasonable mixtures of different crop cultivars can alleviate the limitations triggered by monoculture and low biodiversity (Van & Harfington, ) and enhance the natural enemy species richness (Shi et al ., ). It has been suggested that the increase in crop diversity in agricultural landscape configuration contributes to a general decrease in pest damage on crops (Chaplin‐Kramer et al ., ; Gagic et al ., ); the effect may range from localized reduction of pest abundance to a lower general equilibrium of pest populations at the landscape level (Jonsson et al ., ).…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, we focused on an examination of an ecological approach (habitat diversity through cultivar mixture) toward enhancing vegetation diversity and its associated functional biodiversity in transgenic rice production systems, which could potentially narrow the gap between sustainable agriculture and biodiversity conservation (Tscharntke et al, 2012). Reasonable mixtures of different crop cultivars can alleviate the limitations triggered by monoculture and low biodiversity (Van & Harfington, 2007) and enhance the natural enemy species richness (Shi et al, 2014). It has been suggested that the increase in crop diversity in agricultural landscape configuration contributes to a general decrease in pest damage on crops (Chaplin-Kramer et al, 2011;Gagic et al, 2011); the effect may range from localized reduction of pest abundance to a lower general equilibrium of pest populations at the landscape level (Jonsson et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…As reported in previous studies, herbivores are influenced primarily by vegetation composition within habitats, whereas predators and parasitoids may be more sensitive to changes in field size and habitat arrangement (Stoner & Joern, ; Tscharntke & Brandl, ). In addition, crop species richness significantly affected the pest species richness, although there were no significant effects of the pests' natural enemies on richness (Shi et al , ). In general, herbivores are generally dominated by insects with a relatively lower migration capability, whereas most of the predators show higher mobility.…”
Section: Discussionmentioning
confidence: 99%
“…1996; Lehman and Tilman 2000; Shi et al. 2014a). Indeed, plant diversity has been shown to affect the water cycle in forest ecosystems by differentiating water consumption and recharging groundwater (Sprenger et al.…”
Section: Introductionmentioning
confidence: 99%
“…Mixing different plant species in managed habitats not only can increase the species diversity of other taxa, but also can potentially enhance the stability and productivity of the entire ecosystem (Tilman et al 1996;Lehman and Tilman 2000;Shi et al 2014a). Indeed, plant diversity has been shown to affect the water cycle in forest ecosystems by differentiating water consumption and recharging groundwater (Sprenger et al 2013).…”
Section: Introductionmentioning
confidence: 99%